Immunotherapy, an evolving approach for the management of triple negative breast cancer: Converting non-responders to responders. (February 2018) - Tolba, Mai F.; Omar, Hany A.
Highlights: Immunotherapy is an evolving approach for TNBC. Co-treatment with nab-paclitaxel, CDK4/6 inhibitors or tyrosine kinase inhibitors. Targeting Tim-3/CTLA-4 T-cell suppressor receptors or IDO enzyme. Utilizing STING agonists or depletion of hyaluronan by PEGPH20. The use of TGF-β or HDAC inhibitors as well as radiotherapy. Abstract: Immunotherapy comprises a promising new era in cancer therapy. Immune checkpoint inhibitors targeting either the programmed death (PD)-1 receptor or its ligand PD-L1 were first approved by the Food and Drug Administration (FDA) for the management of metastatic melanoma in 2011. The approval of this class is being extended to include other types of immunogenic tumors. Although breast cancer (BC) was first categorized as non-immunogenic tumor type, there are certain subsets of BC that showed a high level of tumor infiltrating lymphocytes (TILs). Those subsets include the triple negative breast cancer (TNBC) and HER-2 positive breast tumors. Preliminary data from clinical trials presented promising outcomes for patients with advanced stage/metastatic TNBC. While the objective response rate (ORR) was relatively low, it is still promising because of the observation that the patients who respond to the treatment with immune checkpoint blockade have favorable prognosis and often show a significant increase in the overall survival. Therefore, the main challenge is to find ways to enhance the tumor response to such therapy and to convert the non-responders to responders. This will consequently bring new hopes for patients with advanced stage metastatic TNBC and help to decrease death tolls from this devastating disease. In the current review, we are highlighting and discussing the up-to-date strategies adopted at either the preclinical or the clinical settings to enhance tumor responsiveness to immunotherapy.